Role of Low Dose Aspirin for the Prevention of Recurrent Miscarriage - Fida, Ambreen; Hamza, Summaira; Bibi Ruqia; Rehman, Mounazza; Khan, Maleeha; Mir, Sana (Indus Journal of Bioscience Research, 2025)
Background: A considerable percentage of women have recurrent pregnancy loss (RPL), which is defined as two or more consecutive losses. RPL frequently has multiple underlying reasons, such as immunological and thrombotic factors. Since low-dose aspirin (LDA) possesses anti-inflammatory and anti-thrombotic qualities, it has been suggested as a preventative strategy. Objective: The objective of this study is to assess how low-dose aspirin can improve pregnancy outcomes and prevent recurrent miscarriages. Methods: This qualitative study was carried out in a Quetta tertiary care hospital. Purposive sampling was used to choose 120 women who had a history of repeated miscarriages. Semi-structured interviews were used to gather data, which were then subjected to thematic analysis. Findings: 66.7% of the 120 women took low-dose aspirin. Of these, 70.8% went on to have healthy, continuing pregnancies. Better results were obtained with preconception initiation. While mild problems including nausea and stomach discomfort were observed in a small number of individuals, the majority had no side effects. Conclusion: Women who had experienced repeated miscarriages seemed to benefit from low-dose aspirin, particularly if taken before becoming pregnant. It had few adverse effects and was generally well accepted, indicating that it might be a safe prophylactic measure.